Best Answer

x2 + 7x = -2X2+6

3x2 + 7x -6 = 0

(3x-2)(x+3) = 0

Either 3x-2=0

or x+3=0

Either x=2/3

or x=-3

Plug the numbers into the original equation to check.

(2/3)2 + 7(2/3) = -2(2/3)2 +6

4/9 + 14/3 = -8/9 + 6

4/9 + 42/9 + 8/9 - 54/9 = 0

0=0

That one checks out. Let's try the second one.

(-3)2 + 7(-3) = -2(-3)2 + 6

9 -21 = -18 + 6

9 -21 +18 -6 = 0

0=0

The second one checks out also; so both answers are good.

Answer: x = 2/3 or x = -3

Study guides

☆☆

Q: X2 plus 7x equals - 2x2 plus 6?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

x2 + 7x = 2x2 + 6 x2 - 2x2 + 7x = 6 -x2 +7x - 6 = 0 or alternatively x2 - 7x + 6 = 0

x2+7x+3 = 0 Using the quadratic equation formula the solutions are:- x = -6.541381265 or x = -0.4586187349

Assuming that what you're looking for is the values of x: x2 + 7x = 8 x2 + 7x - 8 = 0 (x + 8)(x - 1) = 0 x is equal to either -8 or 1.

x2-7x+12 = 0 (x-3)(x-4) = 0x=3,4

x2+7x-8 = (x-1(x+8)

Related questions

x2 + 7x = 2x2 + 6 x2 - 2x2 + 7x = 6 -x2 +7x - 6 = 0 or alternatively x2 - 7x + 6 = 0

x2+7x=-2x2+6 3x2+7x-6=0 (3x-2)(x+3)=0 3x-2=0 or x+3=0 x=2/3 or x=-3

x2 + x2 = 2x2

x2+7x+12=0 x2+7x=-12 x+Sqaure Root of 7x= 2(SQ Root Symbol)3

The value of x2+7x+10 depends on the value of X. If x=1, then x2+7x+10 = 18 If x=2, then x2+7x+10 = 28 If x=3, then x2+7x+10 = 40 and so forth

6x3 - x2 + 17 = 2x2 + 47 6x3 - x2 - 2x2 = 47 - 17 x2(6x - 1 - 2) = 30 this is the simplest factorisation.

x2 + 7x + 9 = 3 ∴ x2 + 7x + 6 = 0 ∴ (x + 6)(x + 1) = 0 ∴ x ∈ {-6, -1}

3

x2+7x+12

If: y = x2-7x+8 and y = -x2+9x-6 Then: x2-7x+8 = -x2+9x-6 So: 2x2-16x+14 = 0 => x2-8x+7 = 0 Therefore: x = 1 and x = 7 By substitution: x =1, y = 2 and x = 7, y = 8 Points of intersection: (1, 2) and (7, 8)

x2 + x2 = 2x2

x2+7x+3 = 0 Using the quadratic equation formula the solutions are:- x = -6.541381265 or x = -0.4586187349

People also asked

Featured Questions